Ductile fracture of high entropy alloys: From the design of an experimental campaign to the development of a micromechanics-based modeling framework. (November 2022) - Hilhorst, Antoine; Leclerc, Julien; Pardoen, Thomas; Jacques, Pascal J.; Noels, Ludovic; Nguyen, Van-Dung
Abstract: Cantor-type high entropy alloys form a new family of metallic alloys characterized by a combination of high strength and high fracture toughness. An experimental study on the CoCrNi alloy is first performed to determine the damage and fracture mechanisms under various stress states. A micromechanics-based ductile fracture model is identified and validated using these experimental data. The model corresponds to a hyperelastic finite strain multi-yield surface constitutive description coupled with multiple nonlocal variables. The yield surfaces consist of three distinct nonlocal solutions corresponding to three different modes of void expansion within an elastoplastic matrix: a void growth mode governed by a Gurson-based yield surface corrected for shear effects, an internal necking-driven coalescence mode governed by an extension of the Thomason yield surface based on the maximum principal stress, and a shear-driven coalescence mode governed by the maximum shear stress. This advanced formulation embedded in a large strain finite element setup captures the effects not only of the stress triaxiality but also of the Lode variable. In particular, the analysis shows that a failure model accounting for these two invariants of the stress tensor captures the fracture in high-entropy alloys over a wide range of conditions. Highlights: An extensive experimental study is performed on the ternary high entropy alloy. The damage and fracture mechanisms are determined under various stress states. A multi-yield surface micromechanics-based fracture model parameters are identified. The finite strain constitutive model is coupled with multiple nonlocal variables. High-entropy alloy fracture is controlled by stress triaxiality and Lode variable.